Development of a photovoltaic characteristics generator based on mathematical models for four PV panel technologies - Samia Jenkal; Mustapha Kourchi; Driss Yousfi; Ahmed Benlarabi; Mohamed Larbi Elhafyani; Mohamed Ajaamoum; Mhand Oubella (Institute of Advanced Engineering and Science, 2020)
A good study of photovoltaic system requests to have very precise current-voltage characteristic curves of photovoltaic modules for different technologies. The photovoltaic emulator provides an efficient solution to maintain the same current-voltage output of photovoltaic module. It includes three parts: the PV model, the control strategy, and the power converter. This paper provides three classes of modeling and simulation of photovoltaic arrays and presents the synthesis results of the current-voltage characteristic performances obtained by the modeling approaches. The models of the first class are based on electrical circuit model, those of the second class are based on multiple straight lines model, and for the third class, it is based on the look up table. The mathematical model is built using MATLAB/ Simulink, and an experimental bench was carried out to acquire an up-to-date and representative experimental database of four PV panels. This database is used for the validation of these models for the different PV panel technologies under Moroccan meteorological conditions. Following this comparative study, we came to a high agreement between the experimental and simulated current-voltage characteristics for the emulator under study.